Time Distortions in Mind - Vatakis, A. (Brill, 2015)
Time Distortions in Mind brings together current research on temporal processing in clinical populations to elucidate the interdependence between perturbations in timing and disturbances in the mind and brain. For the student, the scientist, and the stepping-stone for further research.